GENETIC PREDICTORS OF RADIATION-INDUCED MORBIDITY IN PROSTATE CANCER PATIENTS - Stanić, Jelena; Stankovic, Vesna; Vostinic, Snezana; Nikitovic, Marina (Medicinski podmladak, 2021)
AbstractCancer survivors often faces adverse effects of treatment, which have a significant impact on morbidity. Normal-tissue side effects following radiotherapy (RT) as one of therapeutic modalities are common and may seriously affect quality of life which is especially important in long-term prostate cancer (PC) survivors. Upgrading in our knowledge in radiation biology have led to the better understanding fact that genetics plays a significant role in determining a patient's predisposition to developing late RT toxicity, leading to the new field of research called “radiogenomics”. With the evolution of DNA sequencing technologies and genomic analysis, radiogenomics has make an appearance as a state-of-the-art science in the field of personalized medicine with the goal of detection the genetic determinants RT adverse reactions. A single-nucleotide polymorphism (SNPs) - based assay could be used to predict the risk of RT adverse effects along with clinical features and treatment factors. Several SNPs have been identified that are associated with late radiation-induced morbidity in PC patients. Most importantly, these SNPs make up genes expressed in the tissues that are likely at the root of these symptoms, including the bladder, rectum, and intestine, which are most exposed to radiation during PC treatment. Genome-wide association studies are likely to lead to an increasing number of genetic polymorphisms that can predict long-term RT complications. Finally, radiogenomics attempts to predict which PC patients will show radiosensitivity or radioresistance, so that radiation oncologists as well as surgeons can change treatment accordingly to reduce side effects or increase the RT effectiveness.
Keywords: biomarkers of radiosensitivity; radiation toxicity; radiogenomics